UNIFORMITY OF RESULTS OF MULTIPLE MEASUREMENT SERIES DURING PREPARING A CONTROL SAMPLE FOR QUALIFICATION TESTS - Нодари Абелашвили; Ника Абелашвили (World Science, 2021)
The work examines the methodology for assessing the homogeneity of the control sample of interlaboratory qualification tests, which is the most important characteristic of determining its status. The criterion for assessing the homogeneity between the characterizing values of the samples is the root mean square deviation and standard deviation of the proficiency test of the control sample with the standard uncertainty of the assigned value, which is a requirement of the ISO 13528 standard. Ignoring this requirement may provoke a false assessment of the participated laboratories taking corrective action.